VALUASI NILAI INTRINSIK SAHAM PT KALBE FARMA TBK (KLBF) - , Asasih Sophia Handadari; , Dr. Su'ad Husnan, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Supported by various Indonesia government policy plans related to public health improvement, pharmaceutical industry is projected to become a prospective industry in the future. PT Kalbe Farma Tbk as a leader in pharmaceutical industry should be considered by investors to be one of their stock investment instruments. However in making a good investment strategy, investor should analyze the fundamental of the stock. The good one analysis is by estimating the intrinsic value of KLBF stock. Intrinsic value of KLBF is projected base on five years estimated financial statements, which is estimated base on the historical financial statements in 2006 until the third quarter of 2011. By using Free Cash Flow to Equity Model (FCFE), intrinsic value of KLBF is estimated at Rp 2,098 per share, it is lower than the current market price which is valued at Rp 3,375 (the closing price on December 21, 2011). Based on the sensitivity analysis of various scenarios of the investor expected return and the terminal growth, it is generaly showed that the intrinsic value of KLBF is lower than its market price. By using the Price Earning Ratio (PER) analysis per third quarter of 2011 affirm that the intrinsic value of KLBF is lower than its market price. Estimated intrinsic value using FCFE valuation model and PER, consistently show that KLBF been overvalued by the market. Based on this conclusion, the investor who already owns KLBF stocks advised to sell the stock to avoid the correction price that could harm investorâs investment.